The unifying, fundamental principles of biogeography: understanding Island Life - Mark Vincent Lomolino (Frontiers of Biogeography)
I describe the set of fundamental principles of biogeography that can serve as an integrative, conceptual framework for unifying and advancing our abilities to explain the geography of life – generally.  I assert that patterns of variation of biotas among regions and across geographic gradients result from the very regular patterns of variation in environmental conditions across the geographic template. This happens through the influence of that variation on the fundamental biogeographic processes (immigration, extinction and evolution), the influence of those fundamental processes on each other, and ecological feedback in the form of interspecific interactions, which influence the fundamental capacities of other species to immigrate, survive and evolve.  I then summarize principal patterns and current theory in island biogeography within the context of the fundamental, unifying principles and show how they can inform a more integrative, conceptual framework for explaining a genuinely comprehensive set of ecological and evolutionary phenomena for insular biotas.